2022
DOI: 10.1002/rcs.2412
|View full text |Cite
|
Sign up to set email alerts
|

Application of 5G technology to conduct tele‐surgical robot‐assisted laparoscopic radical cystectomy

Abstract: Background The aim of this study was to test the effectiveness, safety and stability of the 5G communication technology in clinical laparoscopic telesurgery. Methods An ultra‐remote radical cystectomy (network communication distance of nearly 3000 km) was performed on patient diagnosed with T2N0M0 stage bladder cancer using a domestically produced “MicroHand” surgical robot. Results The network delay, operative time, blood loss, intraoperative complications, postoperative recovery, and hospitalisation time wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Zheng et al performed four laparoscopic telesurgeries in 2020, with a 5G wireless network with a mean round-trip transporting delay of 114 ms and a 1.20% data PLR [30]. Yang et al in 2022 performed an ultra-remote radical cystectomy (network communication distance of nearly 3000 km) on patient diagnosed with T2N0M0 stage bladder cancer through a 5G network with a mean round-trip transporting delay of 104 ms and a 0% data PLR [31]. In 2022, Zhang reported that their team performed Unilateral nephrectomy in 5G wireless network and deterministic networking (DetNet) mode with an average network delay of 27 ms and a 0% data PLR [32].…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al performed four laparoscopic telesurgeries in 2020, with a 5G wireless network with a mean round-trip transporting delay of 114 ms and a 1.20% data PLR [30]. Yang et al in 2022 performed an ultra-remote radical cystectomy (network communication distance of nearly 3000 km) on patient diagnosed with T2N0M0 stage bladder cancer through a 5G network with a mean round-trip transporting delay of 104 ms and a 0% data PLR [31]. In 2022, Zhang reported that their team performed Unilateral nephrectomy in 5G wireless network and deterministic networking (DetNet) mode with an average network delay of 27 ms and a 0% data PLR [32].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, communication networks have been improved, and communication delays and security issues are being resolved 7 . With the widespread use of optical networks and reports of remote robotic surgery using 5G lines, there are high expectations for robotic telesurgery using commercial lines 8 …”
Section: Discussionmentioning
confidence: 99%
“…7 With the widespread use of optical networks and reports of remote robotic surgery using 5G lines, there are high expectations for robotic telesurgery using commercial lines. 8 The biggest hurdle for telesurgery is the problem of delay. The delay time experienced by the surgeon consists of three elements: communication delay, information processing delay, and robot delay.…”
Section: Discussionmentioning
confidence: 99%
“…Total reported average delay, including network latency, image capturing, video (de)coding and mechanical response of the robot, was 264 ms. Recently, the same team presented an ultra-remote telesurgical robot-assisted laparoscopic radical cystectomy on a human patient [ 25 ].…”
Section: Related Workmentioning
confidence: 99%